1982
DOI: 10.1002/j.1460-2075.1982.tb01317.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase activities associated with distinct antigenic forms of polyoma virus middle T-antigen.

Abstract: The tyrosine‐specific protein kinase activity previously described in T‐antigens of polyoma virus immunoprecipitated with anti‐tumour sera has been investigated using monoclonal antibodies. This activity is associated with middle T‐antigen but it can be separated by selective antibody precipitation from the majority of this protein. The difference between active and inactive forms can be accounted for by an antigenic difference at the N terminus of middle T‐antigen molecules. Moreover, the two different mol. w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
28
0

Year Published

1984
1984
1999
1999

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 37 publications
4
28
0
Order By: Relevance
“…Mutation and monoclonal antibody studies have shown that the N-terminal region of MT is involved in the interaction with src-family kinases (Campbell et al, 1995;Cook and Hassell, 1990;Dilworth, 1982;Dilworth and Horner, 1993;Eckhart, 1993, 1995;Kornbluth et al, 1990;Markland and Smith, 1987;Pallas et al, 1986). This area also binds PP2A (Campbell et al, 1995;Eckhart, 1993, 1995;Pallas et al, 1990;Walter et al, 1990) (see Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Mutation and monoclonal antibody studies have shown that the N-terminal region of MT is involved in the interaction with src-family kinases (Campbell et al, 1995;Cook and Hassell, 1990;Dilworth, 1982;Dilworth and Horner, 1993;Eckhart, 1993, 1995;Kornbluth et al, 1990;Markland and Smith, 1987;Pallas et al, 1986). This area also binds PP2A (Campbell et al, 1995;Eckhart, 1993, 1995;Pallas et al, 1990;Walter et al, 1990) (see Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Extracts were prepared and analyzed after immunoprecipitation with anti-polyomavirus middle-T-antigen antibodies (10) as described previously (8).…”
mentioning
confidence: 99%
“…The results (Table 2) demonstrated that this property is completely lost in the PyMLV-infected PC mvc cells, whereas a certain capability to trap iodide (about 15%) is still maintained by the PC PyMLV cells. The hypothesis that differences between PC PyMLV and PC myc PyMLV in the expression of the differentiated and transformed phenotypes could be explained by a different quantitative expression of the middle-T-antigen gene was evaluated by dot-blot RNA and Northern hybridizations with a probe specific for the middle-T-antigen gene (35) and by immunoprecipitation with antibodies against the p56 middle T protein (10). The results demonstrated that specific mRNA for the middle-T-antigen gene is expressed at comparable levels in both PyMLV-infected cell lines (data not shown).…”
mentioning
confidence: 99%
“…5, lanes 5 and 7). To demonstrate that the fractionation procedure does achieve the expected separation, kinase assays were also performed on extracts of cells 5 ,ug of peptide D; 5, 16 ,ug of immunoaffinity anti-C serum; 6, as in 5, plus 5 ,ug of peptide C. Immunoprecipitates were analyzed on 15% polyacrylamide gels and autoradiographed for 7 days. M indicates '4C-labeled marker proteins of apparent molecular weights 94,000, 81,000, 60,000, 53,000, and 40,000.…”
Section: Resultsmentioning
confidence: 99%
“…If tyrosines other than 315 are phosphorylated, mutant middle-T species lacking this residue might be able to accept phosphate in the kinase reaction. Early experiments indicated that d123 middle-T was deficient in acceptor activity, but small amounts of label could be detected in a truncated protein (5,27,28). However, no further analysis of the labeled protein was reported.…”
Section: Resultsmentioning
confidence: 99%